Primera Reunión Ibérica de Intervencionismo Estructural no Valvular: apuntes de un partícipe - Moreno-Martínez, Francisco L. (CorSalud, 2016)
Primera Reunión Ibérica de Intervencionismo Estructural no Valvular: apuntes de un partícipe